2022
DOI: 10.1111/jdv.18294
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence and clinical manifestations of cutaneous adverse reactions following COVID‐19 vaccination: A systematic review and meta‐analysis

Abstract: Although vaccination is widely accepted as an effective method of preventing and controlling the COVID‐19 pandemic, many people are concerned about possible cutaneous side‐effects, which can delay or prevent them from being vaccinated. The objectives of this systematic review were to assess the global prevalence and clinical manifestations of cutaneous adverse reactions following COVID‐19 vaccination. PubMed and Scopus databases were searched for articles published from 1 January 2019 to 31 December 2021, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 302 publications
1
29
0
Order By: Relevance
“…Risk of the second dose of vaccines is another issue of concern. We found similar levels of multiple cutaneous reactions for the first and the second dose, in line with the findings regarding systemic skin reactions reported by Washrawirul et al [ 60 ]. Likewise, another study [ 61 ] focusing on a population experiencing an allergic reaction to the first dose found that the rates of a second reaction with severe immediate and non-severe symptoms were 4.94% (95% CI = 0.93%-22.28%) and 9.54% (95% CI = 2.18%-33.34%), respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Risk of the second dose of vaccines is another issue of concern. We found similar levels of multiple cutaneous reactions for the first and the second dose, in line with the findings regarding systemic skin reactions reported by Washrawirul et al [ 60 ]. Likewise, another study [ 61 ] focusing on a population experiencing an allergic reaction to the first dose found that the rates of a second reaction with severe immediate and non-severe symptoms were 4.94% (95% CI = 0.93%-22.28%) and 9.54% (95% CI = 2.18%-33.34%), respectively.…”
Section: Discussionsupporting
confidence: 93%
“…22 Nevertheless, facial filler reactions are being increasingly reported in this setting. [23][24][25] Previously, dermal filler reactions had been reported after influenza and zoster vaccines. 26,27 As has previously been mentioned, vaccines can precipitate tardive adverse events in the filler injected tissues due to their immunostimulant effects.…”
Section: Vaccine-induced Filler Reactionsmentioning
confidence: 99%
“… 7 A study also reported cutaneous reactions to be secondary to COVID‐19 vaccination, with a 3.8% pooled prevalence (95% confidence interval [CI]: 2.7%−5.3%). 8 These reactions range from exanthema to inflammation, including lichen planus, chilblain‐like lesions, maculopapular or morbilliform rash, erythema multiforme, nonspecific hypersensitivity eruptions, facial dermal filler reactions, reactivation of the varicella‐zoster virus, urticaria, and pityriasis rosea (PR) pityriasis rosea‐like rash (PR‐LE). 9 Inflammatory skin manifestations have been divided, according to their reaction pattern, into five main categories; vascular, red diffuse eruptions; vesicobullous, related with blisters; dermal, affecting deep component in the skin with little or no epidermal change; eczematous; and papulosquamous, scaly, and red conditions.…”
Section: Introductionmentioning
confidence: 99%